Protistal Grazers Increase Grazing on Unicellular Cyanobacteria Diazotroph at Night - Deng, Lixia; Cheung, Shunyan; Liu, Hongbin (Frontiers in Marine Science, 2020)
In this study, we have for the first time analysed diel microzooplankton grazing selectivity on unicellular cyanobacterial diazotroph (i.e. Crocosphaera watsonii WH8501) and non-diazotrophic unicellular microalga (i.e. Chlorella autotrophica). A mixed diet consisting of these two algae was supplied to 4 species of protistan microzooplankton at daytime and night-time, respectively. C. watsonii fixes nitrogen at night-time and showed a stronger diel pattern of cellular C:N ratio than C. autotrophica. All four grazers ingested more C. watsonii at night-time than in daytime, suggesting the diazotroph became more nutritious (inferred by C:N ratio) and thus a preferred prey for grazers when it fixes nitrogen. In particular, Oxyrrhis marina changed from preferring C. autotrophica in daytime to preferring C. watsonii at night-time. The rest grazers showed species-specific grazing preferences, which could be explained by extracellular polysaccharide production of C. watsonii , feeding mode, cingulum size and cell size of grazers.